An Investigation Of Superhydrophobic Waterproofing For Electronic Assembly - Omar, Ghazali; Samsudin, Zambri; Nordin, Mohd Nur Azmi; Kamarolzaman, Anita Akmar; Masripan, Nor Azmmi; Salim, Mohd Azli; Mansor, Muhd Ridzuan; Wu, Jonathan Wei Ping (UTeM, 2019)
Combining the flexibility and stretchability of printed flexible circuits (PFC) such as PET and TPU with water repellent characteristics may improve the functionality of printed circuit for electronic packaging. Water repellent characteristics using ceramic-based coating may protect the surface from degradation and moisture absorption due to the hydrophobicity behavior of the surface after coating.This research seeks to provide insight into characterization and understanding on the effect of thermal on the hydrophobic performance of polymer substrate (PET and TPU) with and without coated with a ceramic coating which is Titanium Dioxide (TiO2) for more robust and vigorous hydrophobiccoating. The annealing temperature was determined by using DSC analysis and four different temperatures have been used in this study. Contact angle and surface roughness characterization were evaluated by self-fabricate contact angle measurement tools and Mitutoyo Profilometer Surftest SJ410. The results reveal that hydrophobicity of uncoated TPU increase and PET decrease after thermally aged. However, after coated with TiO2, both substrate shows further increment in hydrophobicity with contact angle more than 90°. The 2D profile reveals that surface roughness protrusion becomes one of the factors affecting the hydrophobicity of the surface due to liquid-air interfaces under the droplet (air trap) as stated in Wenzel and CassieBaxter theory.